PEMBELAJARAN MATEMATIKA OPERASI HITUNG BILANGAN BULAT DENGAN ALAT PERAGA - yunita wildaniati (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2015)
Mathematics, for the majority of the students, is still considered daunting. One of the topics that they students find it difficult multiplied number. Many of the students failed in comprehensively understanding the multiplied number. The strategy, among others, to make the teaching of multiplied number more effective is by utilizing the props. The purpose of this article is to embed the concept of multiplication and division of integers on elementary school using the props. The props used is positive card and negative card. The props function as a bridge to convey information from the teacher to students correctly.